2016
DOI: 10.1159/000441919
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral β-Amyloid Angiopathy Is Associated with Earlier Dementia Onset in Alzheimer's Disease

Abstract: Background: Cerebral β-amyloid angiopathy (CAA) occurs when β-amyloid (Aβ) is deposited in the vascular media and adventitia. It is a common pathology in the brains of older individuals and has been linked to cognitive decline, but relatively little is known about the influence that CAA has on the clinical manifestation of Alzheimer's disease (AD). The aim of this retrospective analysis was to quantify the effect that CAA had on the manifestation of initial AD-related cognitive change and subsequent progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The Aβ deposited in the vascular walls triggers several ischemia-induced pathogenic molecular pathways, such as oxidative stress, inflammation and increased blood-brain barrier (BBB) permeability, leading to further hemorrhagic complications (Ghiso et al, 2010). A study based on parametric analysis of neuropathological data from the National Alzheimer's Coordinating Centers' dataset suggested that CAA was facilitating early stage dementia and the transition to moderate dementia (Vidoni et al, 2016). In severe CAA cases, Aβ deposition is usually followed by microaneurysms in cerebral blood vessels (Vonsattel et al, 1991), a vascular pathology shared by retinal vascular diseases such as diabetic retinopathy, which can be easily examined by fundoscopy (Friberg et al, 1987;Hellstedt et al, 1996).…”
Section: Retinal Vascular Pathology In Alzheimer's Diseasementioning
confidence: 99%
“…The Aβ deposited in the vascular walls triggers several ischemia-induced pathogenic molecular pathways, such as oxidative stress, inflammation and increased blood-brain barrier (BBB) permeability, leading to further hemorrhagic complications (Ghiso et al, 2010). A study based on parametric analysis of neuropathological data from the National Alzheimer's Coordinating Centers' dataset suggested that CAA was facilitating early stage dementia and the transition to moderate dementia (Vidoni et al, 2016). In severe CAA cases, Aβ deposition is usually followed by microaneurysms in cerebral blood vessels (Vonsattel et al, 1991), a vascular pathology shared by retinal vascular diseases such as diabetic retinopathy, which can be easily examined by fundoscopy (Friberg et al, 1987;Hellstedt et al, 1996).…”
Section: Retinal Vascular Pathology In Alzheimer's Diseasementioning
confidence: 99%
“…Diagnosis of cognitively normal pre-clinical AD followed the recommendations from NIA and the Alzheimer's Association workgroup (Sperling et al, 2011). The protocol for determination of amyloid elevation is detailed elsewhere (Vidoni et al, 2016). The average time between administration of PET scan and EEG assessment was 1090 (479) days.…”
Section: Participantsmentioning
confidence: 99%
“…Severe CAA can impair blood flow and produce ischemic lesions or small infarcts, while severe CAA can lead to lobar hemorrhages typically affecting the frontal and occipital lobes [18]. The preponderance of CAA in AD and its association with an earlier age of onset support its role on the disease process, independently contributing to clinical presentations of AD [46, 49, 50]. Several methods have been proposed to score severity of CAA burden, and imaging techniques are being developed to differentiate CAA from plaque amyloid [46].…”
Section: Introductionmentioning
confidence: 99%